A review of the legislations in controlling precursors in Malaysia / Hasrolnizam Abdullah, Mohd Yusri Che Musa and Tommy Buja - Abdullah, Hasrolnizam; Che Musa, Mohd Yusri; Buja, Tommy (2009)
Precursor control is relatively new in many countries including Malaysia. However, in Malaysia the diversion of the precursors by the drugs syndicate has become a major concern. This can be identified by the number of clandestine drug labs discovered throughout the country recently by the Police. The diversion of the precursors needs to be fully addressed so that the illicit drugs manufacturer will not be able to easily abuse the system. Thus the legislations that control the precursors and the enforcement agencies that enforce the legislations will be reviewed to identify their strengths and weaknesses. This research is set out to examine the legislations and also the agencies involved in the control of precursors in the country through the qualitative research methodology where the information is gathered from journals, reports, articles and books. A semi structured interview of the personnel from the relevant agencies is also conducted. From this research it has been discovered that the existing legislations are not designed specifically to control precursors. The Poisons Act 1952 (Act 366) was initially initiated to control a wide range of chemicals including the chemicals that have medicinal value. The Act is considered sufficient in controlling the importation, sale or supply, transporting, labelling and recording of precursors but lacks in controlling the exportation, manufacturing, possession, usage and disposal of precursors. These weaknesses of the Act in controlling precursors should be reviewed and resolved by the government. Thus, there is a need to improve the current legislations and the enforcement approaches in regards to the control of precursors in Malaysia.